Use of supplementary rotor current control in DFIG to augment fault ride through of wind farm as per grid requirement - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2011)
Fixed speed wind turbine generator system that uses induction generator (IG) has the stability problem similar to the step-out phenomenon of a synchronous generator during grid fault. On the other hand, doubly fed induction generator (DFIG) can control its real and reactive powers independently while being operated in variable speed mode. This paper proposes a new control strategy using DFIGs for stabilizing wind farms composed of DFIGs and IGs, without incorporating additional FACTS devices. A new control scheme of limiting the rotor current of the DFIGs during grid fault was proposed. Simulation analysis by using PSCAD/EMTDC shows that the DFIGs can effectively stabilize the IGs and hence the entire wind farms through the proposed control scheme by providing sufficient reactive power to the system.